Unlocking the pharmacological potential of Brennnesselwurzel (Urtica dioica L.): an in-depth study on multifaceted biological activities - Amr Elkelish; Abdelghafar M. Abu-Elsaoud; Alaa M. Alqahtani; Mohammad El-Nablaway; Norah Al harthi; Najwa Al harthi; Sulaiman Lakoh; Essa M. Saied; Mai Labib (BMC Complementary Medicine and Therapies)
Abstract Brennnesselwurzel (Urtica dioica L.) is recognized for its diverse pharmacological properties. With a range of chemical constituents, such as vitamins, minerals, phenolic compounds, fibers, and amino acids, Brennnesselwurzel (BWE) has a long history of traditional medicinal use in Europe and Asia. The correlation between a plant's metabolite composition and its activity can vary depending on considerations such as geographic location, environmental conditions, and genetic variations. In the present study, we explore the phytochemical profile and biological activity of the 70% acetone extract of the BWE plant. The chemical profile of the BWE extract was explored using several techniques, including amino acid analyzer, HPLC, GC–MS, and other colorimetric analysis. The antioxidant activity of the BWE extract was assessed by evaluating the total antioxidant, free radical scavenging activity (DPPH, ABTS, H2O2), and metal chelating scavenging activity (FRAP, CUPRAC, metal chelating). Furthermore, we assessed the antimicrobial and antiproliferation activities of the BWE extract against 29 microbial strains and 15 cell lines, respectively. Our phytochemical analyzes revealed that the BWE extract has a unique profile of metabolites including amino acids, flavonoids, phenolics, volatile oils, lipids, and vitamins. The BWE extract showed a total antioxidant capacity of 30.94 ± 1.58 mg GAE/g, together with potential free radical scavenging activity towards ABTS (IC50 = 153.51 ± 3.97 µg/ml), DPPH (IC50 = 195.75 ± 5.91 µg/ml), and H2O2 (IC50 = 230.67 ± 5.98 µg/ml). Although the BWE extract showed no significant antifungal activity, our findings revealed that the BWE extract possesses substantial antibacterial activity against Staphylococcus epidermidi, Streptococcus mutants, Enterococcus faecalis, Micrococcus sp., Klebsiella pneumonia and Porphyromonas gingivalis. Furthermore, the BWE extract demonstrated potential antiproliferative activity toward a panel of cancer cell lines with a high selectivity index. Among the cells examined, the BWE extract exhibited significant cytotoxic activity toward HCT-116, A-549, MDA-MB-231 cells with IC50 of 15.11, 15.32, 15.79 µg/mL, respectively, while it possessed no significant cytotoxic activity towards WI-38 cells (IC50 119.62 µg/mL). Taken together, our findings reveal that BWE extract possesses a wide spectrum of biological activities, including antioxidant, antibacterial, and antitumor activities, and could be considered for further research to explore its potential as a natural plant-based supplement for human diseases.